Bibliometric Analysis Of Research Publications Related To At-Tazkir And At-Ta’Nith In Al-Qur’An - Maryam Mokhtar; Aisyah Humairaa Muhammad Faisal; Tg. Ainul Farha Tg. Abdul Rahman (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI009 90-99